2019
DOI: 10.1016/j.heliyon.2019.e02067
|View full text |Cite
|
Sign up to set email alerts
|

Perception of a “good death” in Thai patients with cancer and their relatives

Abstract: Background Understanding the perceptions regarding what constitutes a "good death" among cancer patients and their families could help healthcare teams to ensure proper palliative and supportive care. Objectives To demonstrate and compare the wishes cancer patients and the perceptions of their relatives regarding end-of-life care, and to identify factors associated with patients' preferences regarding place of death. Methods A sample of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 34 publications
(65 reference statements)
2
34
0
1
Order By: Relevance
“…This nding is consistent with those of a prior study on Northern Thai patients with a terminal illness; they desired that both physicians and relatives be involved in deciding the EoL care they received [13]. Furthermore, this nding supports the report of a former study that Asian patients were more likely to have their family involved in medical decision-making rather than exercising full autonomy or decide only by themselves like most American and European patients do [1,15,16]. Concerning this matter and in light of this nding, Thai physicians should ask their patients whether they wish to receive information regarding their health conditions and treatment and to what extent, as well as whether they would like to be involved in making decisions related to their care or prefer that their families handle such matters [17].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This nding is consistent with those of a prior study on Northern Thai patients with a terminal illness; they desired that both physicians and relatives be involved in deciding the EoL care they received [13]. Furthermore, this nding supports the report of a former study that Asian patients were more likely to have their family involved in medical decision-making rather than exercising full autonomy or decide only by themselves like most American and European patients do [1,15,16]. Concerning this matter and in light of this nding, Thai physicians should ask their patients whether they wish to receive information regarding their health conditions and treatment and to what extent, as well as whether they would like to be involved in making decisions related to their care or prefer that their families handle such matters [17].…”
Section: Discussionsupporting
confidence: 88%
“…2) Inquiry regarding experiences with EoL care involving their relatives, which consisted of questions on experiences related to seeing someone die and being an EoL caregiver. Each item was rated as 'yes' or 'no'; the attitude toward experiences with the death of a relative was rated as 'satis ed', 'unsatis ed', or 'neither satis ed nor unsatis ed', meanwhile the attitude toward remembered death was rated as 'agree', 'disagree', or 'neither agree nor disagree' [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found similar results, especially regarding the negative impact of introversion on health ( Perry et al., 2018 ). Having significant relationships with friends, partners, and even healthcare professionals seems to be important to achieve an optimal emotional and psychological adaptation to the disease ( Chindaprasirt et al., 2019 ; Rokach, 2019 ; Saita et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%